PW 1704 Costing of injury burden can trigger planning in developing countries. (November 2018) - Verma, Eshant; Verma, Pramod Kumar
Abstract : Background: Injury is still not recognized in developing countries as public health problem. We have to compare cost of injury burden with the cost of preventive strategies. Costing is a powerful persuader/tool for decision-makers. Objective: Cost calculation and cost effectiveness for injury prevention. Methods: (A) Cost of injury has different aspect for calculation: 1.Direct versus Indirect Cost: Direct cost is actual expenses and indirect cost includes cost of pain, suffering, loss of productivity due to disability (DALYs) 2.Economic burden of specific determinant of injury. 3.External cost of injury: Cost involved in modification of specific determinant of injury by which burden of injury can be reduced. (B) Injury cost can be calculated by different Method: 1. Operational Method of Costing: Actual cost incurred during injury management. Cost of injury=Cost per injured ×no. of iterations/year. GNP loss of nations by injury=cost of nation per injured ×magnitude of injury/year. 2. Incidence vs Prevalence cost: 3. Post vs Continuous costing: 4. Job vs Process costing: 5. Fix vs Variable cost: 6. Standard vs Actual cost: Findings: Annual incidence rate of injury in Delhi was 116.7/1000. Cost per injury management was Rs. 2627.2. So out of annual per capita income of Rs. 3120.0 (US$ 67.8) in India, 8.9% of per capita income incurred on injury. Gross Nation Product (GNP) loss of India due to injury was 124.1 billion Indian rupees or US$ 2.7 billion. This cost may increase manifold if we include indirect cost of injury in term of DALYs. Conclusion: Injury burden needs urgent planning. Policy implication: Cost-effectiveness of injury prevention program can only be realized if we compare cost of injury burden and cost of prevention strategies.